Poured from the Sky: The Story of Traditional Ecological Knowledge in Cérékang Forest Conservation - Muhammad Akhmar, Andi; Rahman, Fathu; Supratman, Supratman; Hasyim, Husain; Nawir, M. (Forest and Society, 2022)
The Cérékang people are often used as an example of how Indigenous Peoples successfully carry out traditional conservation of customary forests. This article aims to investigate the conditions that sustain the forest conservation in Cérékang by using Berkes’s (2008) concept of traditional ecological knowledge (TEK) and Houde’s (2007) six dimensions of TEK as the framework. Data collections were obtained through literature review, direct observation, in-depth interviews, and focus group discussions with key informants. The results of the study are as follows: First, the mythical construction around the area of forest is connected to their cosmology and stories of origin associated with the La Galigo epic, and the Cérékang people have developed protective attitudes towards forests consistent with the term “sacred ecology”. Second, such an attitude is endured by the ethics that respect the intimate relationship between humans, nature, and spiritual realms, which is subsequently manifested through prohibitions to enter the sacred forest except for ritual. This implies that the Cérékang people rely on symbolic knowledge, not technical knowledge, to protect the forest. The protected forest does not only provide cultural ecosystem services but also regulates services that indirectly benefit the Cerekang People such as flood prevention. Yet, the uncertain legal status of the sacred forest and the activities of a mining company around the area pose threats for continued conservation efforts. Consequently, to exercise direct control over the sacred forest area, new community organizations are integrated with customary institutions formed with support from NGOs, local government, and universities. This can be seen as their adaptation strategy to survive and conserve the forest amid ongoing challenges.